SISTEM PELAPORAN KUNJUNGAN DEBT COLLECTOR KARTU KREDIT BERBASIS TRACKING GPS - Yusup Saepulloh; Dadi Rosadi; Asep Ririh Riswaya (STMIK Mardira Indonesia, Bandung, 2021)
This study aims to create a system according to the needs of collectors, optimize the input of visit reports that can be accessed on each collector's cellphone and there is information on the results of bills from each collector both from the results of daily bills and the final results of billing and TL (Team Leader) can monitor collector visits via GPS tracking. The benefits of this research can be a solution to the problem of collector visits and help the Team Leader of PT. Bank Central Asia Tbk so that work becomes more effective and can make it easier for collectors to input visit reports. Descriptive research method with data collection techniques, interviews with the authorities. The location of this research is in Bank Central Asia (BCA), especially in the credit card billing section. The result of the research is the development of a GPS tracking-based credit card debt collector visit report system to make it easier for Team Leaders to monitor and optimize collector time to perform in the field.Keywords: GPS Tracking, Collector, Visit Report, Credit Card.DOI : http://doi.org/10.5281/zenodo.4958031